2021
DOI: 10.1002/jtr.2454
|View full text |Cite
|
Sign up to set email alerts
|

Coping as a community: Recovery experiences of a tourism‐reliant area following a tsunami in Indonesia

Abstract: Despite the burgeoning amount of tourism recovery research, there is a dearth of studies that explore communal coping. To address this gap, this study examined the communal coping of a tourism‐reliant community in Indonesia that was destroyed by a tsunami using the Participatory Research Action (PAR) paradigm. It employs Photovoice augmented with mobile data collection using Survey123 from ESRI. The findings identified three phases of communal coping: losing the daily routine, reviving routines, and living wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…Tourism-led growth (Seetanah & Fauzel, 2019 ; Walker, 2019 ; Holden, 2019 ; Gössling et al, 2020 ) can be enhanced with technology (Fyall & Garrod, 2019 ) and temporary state funding (Nicola et al, 2020 ) amidst crises and disasters to promote small business economic resilience as resilient organizations towards business continuity (Brown et al, 2018 ). Current studies emphasized the need for more economic support (Dayour et al, 2020a , 2020b ; Zhai & Shi, 2021 ) for tourism MSMEs as the sector struggles with experimentation, diversification, and business shift (Nuñez & Musteen, 2020 ; Dayour et al, 2020a , 2020b ; Pyke et al, 2021 ; Cahyanto et al, 2021 ) to maximize scarce resources (Coles et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Tourism-led growth (Seetanah & Fauzel, 2019 ; Walker, 2019 ; Holden, 2019 ; Gössling et al, 2020 ) can be enhanced with technology (Fyall & Garrod, 2019 ) and temporary state funding (Nicola et al, 2020 ) amidst crises and disasters to promote small business economic resilience as resilient organizations towards business continuity (Brown et al, 2018 ). Current studies emphasized the need for more economic support (Dayour et al, 2020a , 2020b ; Zhai & Shi, 2021 ) for tourism MSMEs as the sector struggles with experimentation, diversification, and business shift (Nuñez & Musteen, 2020 ; Dayour et al, 2020a , 2020b ; Pyke et al, 2021 ; Cahyanto et al, 2021 ) to maximize scarce resources (Coles et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, tourism studies confirmed that social capital is positively linked to destination resilience (Jia et al, 2020;Cahyanto et al, 2021). One pivotal study examined the transnational social capital maintained by British retirees in Spain and the resultant VFR tourism flows (Casado-Dı ´az et al, 2014).…”
Section: Diaspora As Social Capital For Destination Recoverymentioning
confidence: 96%
“…This method can create a more resilient and sustainable tourism industry that benefits the community. During natural calamities or pandemics, social coping behavior helps tourism survive (Cahyanto, Kingsbury, Widodo, Puspita, Harnadi, 2021). Hotels should work with the community to create coping strategies and support structures to recover from disasters.…”
Section: Use Of National and Local Resourcesmentioning
confidence: 99%
“…This strategy can make tourism more resilient and sustainable for the town. Social coping helps tourism survive natural disasters and pandemics (Cahyanto et al, 2021). Hotels and the community should build coping methods and support networks to help people recover.…”
Section: Level Of Tourism Resilience Of Resort Hotels In Calabarzonmentioning
confidence: 99%